Continuous Flow Fabrication of Block Copolymer–Grafted Silica Micro‐Particles in Environmentally Friendly Water/Ethanol Media. Issue 2 (9th October 2018) - Ye, Piaoran; Cao, Peng‐Fei; Chen, Qiyi; Advincula, Rigoberto
Abstract: Polymer‐grafted inorganic particles (PGIPs) are attractive building blocks for numerous chemical and material applications. Surface‐initiated controlled radical polymerization (SI‐CRP) is the most feasible method to fabricate PGIPs. However, a conventional in‐batch reaction still suffers from several disadvantages, including time‐consuming purification processes, low grafting efficiency, and possible gelation problems. Herein, a facile method is demonstrated to synthesize block copolymer–grafted inorganic particles, that is, poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMEMA)‐ b ‐poly( N ‐isopropylacrylamide) (PNIPAM)–grafted silica micro‐particles using continuous flow chemistry in an environmentally friendly aqueous media. Immobilizing the chain transfer agent and subsequent SI‐CRP can be accomplished sequentially in a continuous flow system, avoiding multi‐step purification processes in between. The chain length (MW) of the grafted polymers is tunable by adjusting the flow time or monomer concentration, and the narrower molar mass dispersity ( Ð < 1.4) of the grafted polymers reveals the uniform polymer chains on the particles. Moreover, compared with the in‐batch reaction at the same condition, the continuous system also suppresses possible gelation problems. Abstract : Continuous flow chemistry and polymerization have advantages with grafting polymers and block copolymers from particle surfaces. Surface‐initiated polymerization via living free radical RAFT mechanism enables control of chain length (MW) and copolymer block length. The reaction is facile and does not require significant work‐up conditions.